Potential therapeutic effect of citrus peel components against cancer / Nursyifa’ Yusri and Hisham Mohd Nooh - Yusri, Nursyifa’; Mohd Nooh, Hisham (2021)
Cancer is a globally significant death cause. However, drug development for cancer treatment has always been associated with side effects and several limitations in applications. Citrus fruit belonging to the family Rutaceae has many health-promoting activities such as anticancer, antitumor, anticarcinogenic, anti-inflammatory and antiproliferative which have been linked with many active compounds while at the same time is highly consumed worldwide. Citrus peels that are generally discarded as waste to the environment can act as potential therapeutic resources in addition to their low-cost and easy availability. Flavonoids are bioactive components in the citrus peel that are largely related to anticancer potential. Among the flavonoid derivatives, particularly flavone glycosides and polymethoxy flavones have shown potent anticancer properties as found in many scientific studies. Action mechanism of flavonoids modulated including apoptosis, metastasis, angiogenesis, cell proliferation and cell cycle regulation. These bioactive rich citrus extracts also have been utilized as a chemotherapeutic agent against the growth of different cancer cells such as breast cancer, colon cancer, prostate cancer, and others. This review highlights new research in the field, especially the nanoparticles from citrus peel used to treat cancer and the signal pathways or action mechanisms modulated by potent compounds in citrus peel on the cancer cell line. Besides, this study also showed the great potential of citrus peel as a plant-based substance to be developed as the source of a chemopreventive agent in suppressing and inhibiting the cancer cells growth. Therefore, further study about the citrus peel potential needs to be conducted.